A new species of Mesembrinella (Diptera: Calliphoridae: Mesembrinellinae) from Colombia (2013)
ABSTRACT: Mesembrinella is a Neotropical genus with only three species reported for Colombia: M. apollinaris, M. bicolor y M. umbrosa. This paper describes a new species of the genus; Mesembrinella patriciae sp. nov. which is found in the departments of Antioquia, Caldas, Norte de Santander, Quindío, Risaralda and Santander (Central and Eastern Andean mountain range) between 1,900-2,800 masl. Identification key of the species of Mesembrinella and description of the male and female of the new species are provided along with illustrations of the terminalia.